Faktor-Faktor Yang Berhubungan Dengan Pemberian ASI Eksklusif Pada BayiDi Wilayah Kerja Puskesmas Huraba Kabupaten Tapanuli Selatan - Pebrianthy, Lola; Aswan, Yulinda; Wari Harahap, Yanna (Sekolah Tinggi Ilmu Kesehatan YARSI Mataram, 2021)
Exclusive breastfeeding is that babies are only breastfed for six months without additional fluids and other foods except medicated syrup. The coverage of exclusive breastfeeding in Indonesia in 2018 of 65.16% has not reached the national target (80%), the coverage of exclusive breastfeeding in working area of Puskesmas Huraba in Tapanuli Selatan Regency in 2019 is around 23.2%. This study aims to determine the factors associated with exclusive breastfeeding in infants in Puskesmas Huraba, Tapanuli Selatan Regency in 2020. This type of research is quantitative with a cross sectional design. The population of all mothers who have babies aged 6-12 months, the sample is 57 total sampling techniques. The results showed that there was no relationship between education (p= 0,250), occupation (p=0,920) and attitude (p=0,568) with exclusive breastfeeding. There was a relationship between knowledge (p=0,049) and socio-cultural (p=0.013) with exclusive breastfeeding in the work area of Puskesmas Huraba. It is suggested to health workers at Puskesmas Huraba to increase health promotion about the importance of exclusive breastfeeding for babies so that mothers are more motivated to provide exclusive breastfeeding and mothers should be more proactive in seeking information about exclusive breastfeeding and the benefits of exclusive breastfeeding to increase their knowledge about exclusive breastfeeding.